Engineered whole cut meat-like tissue by the assembly of cell fibers using tendon-gel integrated bioprinting - Kang, Dong-Hee; Louis, Fiona; Liu, Hao; Shimoda, Hiroshi; Nishiyama, Yasutaka; Nozawa, Hajime; Kakitani, Makoto; Takagi, Daisuke; Kasa, Daijiro; Nagamori, Eiji; Irie, Shinji; Kitano, Shiro; et al. (Nature communications, 2021)
With the current interest in cultured meat, mammalian cell-based meat has mostly been unstructured. There is thus still a high demand for artificial steak-like meat. We demonstrate in vitro construction of engineered steak-like tissue assembled of three types of bovine cell fibers (muscle, fat, and vessel). Because actual meat is an aligned assembly of the fibers connected to the tendon for the actions of contraction and relaxation, tendon-gel integrated bioprinting was developed to construct tendon-like gels. In this study, a total of 72 fibers comprising 42 muscles, 28 adipose tissues, and 2 blood capillaries were constructed by tendon-gel integrated bioprinting and manually assembled to fabricate steak-like meat with a diameter of 5 mm and a length of 10 mm inspired by a meat cut. The developed tendon-gel integrated bioprinting here could be a promising technology for the fabrication of the desired types of steak-like cultured meats. Mammalian cell-based cultured meat has mostly been unstructured, leaving a demand for artificial steak-like meat. Here the authors present an assembled steak-like tissue of bovine skeletal muscle, adipose tissue, and blood capillary tissue fabricated by tendon-gel integrated printing technology.